Anthropogenic cause of range shifts and gene flow between two grasshopper species revealed by environmental modelling, geometric morphometrics and population genetics. Issue 5 (19th February 2018) - Sivyer, Louisa; Morgan‐Richards, Mary; Koot, Emily; Trewick, Steven A.
Abstract: The range of a species is controlled by biotic and abiotic factors; both could have changed recently due to human activity. We used environmental modelling, morphometric and genetic data to interpret ecological responses at the species boundary of a pair of New Zealand grasshoppers with very different ranges; one widespread ( Phaulacridium marginale ) and one restricted to semi‐arid central/southern South Island ( Phaulacridium otagoense ). Climate‐ and habitat‐based distribution models for grasshoppers in the past (last glacial maximum), present and future (2070), in concert with modelling of vegetation patterns imply range and demographic expansion of P. marginale and stability of P. otagoense . mtDNA sequence revealed four main lineages with pronounced differences in genetic diversity and geographical range. The widespread lineage associated with P. marginale revealed a signature of range expansion but regionally restricted lineages were geographically structured at a fine scale. Within the narrow geographical range of P. otagoense, three mtDNA lineages resulted in high diversity, more typical of large stable populations. Geometric analysis of pronotum shape identified individuals from a region of sympatry with mixed characteristics. Mismatch of phenotype, mtDNA lineage and nuclear DNA sequence indicates introgression between grasshopper species now in contact. This appears to be accompanied by P. otagoense range reduction through ecological competition. Deforestation by people starting ∼800 years ago best explains range change and resulting hybridisation of these grasshoppers. Anthropogenic habitat modification can have indirect consequences on insect biodiversity and conservation by enabling introgression between formerly separate populations and species.